Corrigendum to: The relationship between inquiry-based teaching and students' achievement. New evidence from a longitudinal PISA study in England. Learning and Instruction (2019) 35 – 44. (August 2022) - Jerrim, John; Oliver, Mary; Sims, Sam
Abstract : The authors and journal regret that the printed version of the above article contained a number of errors, in which statements which had been blinded for review were not revealed for the publication. These were references to the authors' own prior work. The correct and final version, with complete references, follows. The authors and journal would like to apologise for any inconvenience caused.